2010
DOI: 10.1016/j.regpep.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Intraneuronal angiotensinergic system in rat and human dorsal root ganglia

Abstract: To elucidate the local formation of angiotensin II (Ang II) in the neurons of sensory dorsal root ganglia (DRG), we studied the expression of angiotensinogen (Ang-N)-, renin-, angiotensin converting enzyme (ACE)-and cathepsin D-mRNA, and the presence of protein renin, Ang II, Substance P and calcitonin gene-related peptide (CGRP) in the rat and human thoracic DRG. Quantitative real time PCR (qRT-PCR) studies revealed that rat DRG expressed substantial amounts of Ang-N-and ACE mRNA, while renin mRNA as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
69
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 66 publications
9
69
1
2
Order By: Relevance
“…RT-PCR using specific primers and emulsion autoradiography of the hybridized DRG sections with selective riboprobes revealed the presence of AT 1 mRNA in the rat DRG (Patil et al 2010;Pavel et al 2008). Similarly, our immunofluorescence results have shown that AT 1 is expressed in different extent to most of the DRG neuronal cells.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…RT-PCR using specific primers and emulsion autoradiography of the hybridized DRG sections with selective riboprobes revealed the presence of AT 1 mRNA in the rat DRG (Patil et al 2010;Pavel et al 2008). Similarly, our immunofluorescence results have shown that AT 1 is expressed in different extent to most of the DRG neuronal cells.…”
Section: Discussionsupporting
confidence: 79%
“…Recently, the presence of intraneuronal angiotensinergic system and Angiotensin II receptor type 1 (AT 1 ) has been documented in rat dorsal root ganglia (DRGs) (Patil et al 2010;Pavel et al 2008;Tang et al 2008), the structures containing primary afferent neurons that convey sensory information from periphery to the CNS. Our previous study showed that AT 1 binding and mRNA, determined by in situ hybridization with specific riboprobes, are localized to numerous neuronal cells in the DRGs .…”
Section: Introductionmentioning
confidence: 99%
“…Although chymase can form Ang II by cleaving Ang I (Kirimura et al, 2005), its mRNA was also absent from the lumbar dorsal spinal cord. Similar to the spinal cord, the mRNA for cathepsin D, but not renin, is reported to be expressed in the DRG (Patil et al, 2010). Therefore, we can speculate that cathepsin D cleaves AGT to Ang I, which is in turn converted to Ang II by ACE in the spinal cord.…”
Section: Discussionmentioning
confidence: 80%
“…In both rat and human dorsal root ganglia (DRGs) Ang II is colocalized in two known regulators for nociception and sensory transmission: substance P and calcitonin gene-related peptide (Patil et al, 2010). We have previously demonstrated that when mice are administered Ang II intrathecally, p38 mitogenactivated protein kinase (MAPK) is phosphorylated through AT1 receptors, leading to nociceptive behavior (Nemoto et al, 2013(Nemoto et al, , 2015a.…”
Section: Introductionmentioning
confidence: 99%
“…Il transmet par l'Ang II un effet vasoconstricteur au niveau des vaisseaux médié par ses récepteurs AT 1 . Grâce à l'utilisation d'un anticorps monoclonal hautement spécifique (Mab 4B3) et une méthodologie immunocytologique adaptée, nous avons réussi à dépister un sous-groupe de neurones avec un phénotype Ang II-positif parmi les neurones du ganglion céliaque, trigé-minal et spinal chez le rat comme chez l'homme [4][5][6]. Nous avons également retrouvé un phénotype Ang II-positif parmi les fibres autonomes innervant le coeur, les artères et le rein dans plusieurs espèces (rat, cochon et homme) [4,7,8].…”
Section: Introductionunclassified